The global well-posedness of the modified quasi-geostrophic equation in frequency spaces. (May 2015) - Ru, Shaolei; Chen, Jiecheng
Abstract: We show that the solution, θ ( x, t ), of the modified quasi-geostrophic equations exists globally (i.e., θ ( x, t ) ∈ L ∞ ( R + ; F L 1 r, 0 ) ∩ L 1 ( R + ; F L 1 r, α ) ), if the initial data ‖ θ 0 ( x ) ‖ F L 1 r, 0 < k 2 r + α + 3 .